EVALUATION FEASIBILITY AND BUSINESS DEVELOPMENT STRATEGY ENLARGEMENT WHITE SHRIMP (LITOPENAEUS VANNAMEI) AT DUKUHTUNGGAL VILLAGE GLAGAH SUB DISTRICT LAMONGAN - Lutfi, Ika Maulana; Hermawan, David; Zubaidah, Anis (xxxx-xxxx)
This research aims to analyze the financial feasibility and formulating business development strategies enlargement of White shrimp at Dukuhtunggal Village Sub district Glagah Lamongan. The research using survey method. The sampling method used snowball sampling by the number of respondents as many as 18 people. The result showed that the business of enlarging white shrimp enlargement enterprise development deserves to be implemented and developed, because of the results of the assessment in accordance with the investment criteria Net Present Value (NPV) reached Rp 283.927.334, Net Benefit Cost Ratio (Net/B/C) by 28, Internal Rate of Return (IRR) reached 645.5%, the value of payback period  of 0.37 or three months of seven days and the Profitability index (PI) of 1.53. Business development strategy is known through proceeds from the matrix IFE and EFE with a total score of 3.341 and 3.272. Matrix IE shows the position of the company located on the cell to one which means grow and build so that the appropriate strategy to be applied is the intensive strategy i.e., market penetration, market development, product development and integration strategies. The formulation of the strategy produces eight alternative development strategies i.e., an increase in production capacity, strengthening the institutional role, leveraging capital access, empowerment of farmers, increase the use of quality seeds, weaves cooperation with suppliers, maintaining the condition of the infrastructure, and improve the implementation and monitoring of standard operational procedures. Keywords: Litopenaeus vannamei, feasibility, strategy enlargement